2022
DOI: 10.1242/jcs.258809
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 activation attenuates thrombin-induced blebbing in breast cancer cells

Abstract: Cancer cells exploit a variety of migration modes to leave primary tumors and establish metastases, including amoeboid cell migration, which is typically reliant on bleb formation. Here we demonstrate that thrombin induces dynamic blebbing in the MDA-MB-231 breast cancer cell line, and confirm that PAR1 activation is sufficient to induce this effect. Cell confinement has been implicated as a driving force in bleb-based migration. Unexpectedly, we find that gentle contact compression, exerted using a custom bui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 89 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…We therefore exposed islet cells to two forms of mechanical stimulation, mild compression and fluid flow, while recording Ca 2+ concentration changes in the primary cilia by confocal microscopy. Compression was accomplished using the cell press ( O’Callaghan et al, 2022 ), a piezomotor-controlled manipulator that linearly translates a flexible polydimethylsiloxane (PDMS) compression pillar, which was fitted to the stage of the microscope. Using this device, we compressed islets expressing the cilia-targeted Ca 2+ indicator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore exposed islet cells to two forms of mechanical stimulation, mild compression and fluid flow, while recording Ca 2+ concentration changes in the primary cilia by confocal microscopy. Compression was accomplished using the cell press ( O’Callaghan et al, 2022 ), a piezomotor-controlled manipulator that linearly translates a flexible polydimethylsiloxane (PDMS) compression pillar, which was fitted to the stage of the microscope. Using this device, we compressed islets expressing the cilia-targeted Ca 2+ indicator.…”
Section: Resultsmentioning
confidence: 99%
“…Islet compression experiments were performed with a custom-built manipulator referred to as the cell press ( O’Callaghan et al, 2022 ). The device consists of 3D-printed parts, a linear piezoelectric positioner (SLC-1730, SmarAct GmbH), which is operated through a MCS2 manual controller (SmarAct), and a PDMS compression pillar, which was cast from a 3D-printed mold.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have suggested that Piezo1 is involved in regulating many of diseases, including the infectious inflammation and cancer ( Nguetse et al, 2020 ; Choi et al, 2019 ; Nonomura et al, 2018 ; Chang et al, 2019 ; Xie et al, 2022 ; Kuriyama et al, 2022 ; O’Callaghan et al, 2022 ; Liu et al, 2021 ). Piezo1 modulates macrophage polarization and stiffness sensing, which are related to calcium influx and the promotion of macrophage activation by actin ( Atcha et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elimination of Piezo1 in myeloid cells could prevent cancer [42] Functional relevance of Piezo1 in cancer. In recent years, a number of studies have shown that Piezo1 plays an important role in regulating the occurrence and development of various tumors, such as stomach cancer [34], colon tumors [36], hepatocellular carcinoma [37], lung cancer [38,39], breast carcinoma [40], oral squamous cell carcinoma [41], and pancreatic ductal adenocarcinoma [42]. Table 2 shows various signaling pathways related to the induction of key regulators of Piezo1 channel proteins, in response to mechanical stimulation, which provides new research ideas for subsequent tumor treatment.…”
Section: Piezo1 Impacts Tumor Progressionmentioning
confidence: 99%
“…Piezo1 activation inhibits thrombin-induced phosphorylation of the ezrin, radixin, and moesin (ERM) proteins, which are involved in the foaming process. In the development of new drugs, Piezo1 activation could offer a novel way to inhibit thrombinase-induced blistering in breast cancer cells [40].…”
Section: Piezo1 Impacts Tumor Progressionmentioning
confidence: 99%